'Who said we play to hit each other?' Early childhood teachers' responses to children's transgressions. Issue 2 (3rd April 2021) - Bustamante, Andrea; Maldonado-Carreño, Carolina; González, Olga Lucía; Navia, María Angélica; Restrepo, Eliana Carolina; Torres, Diana Fernanda
ABSTRACT: One hundred and ninety-eight hours of teacher-student interactions following transgressions in 109 early childhood classrooms in Colombia were observed to describe: (1) the types of responses teachers used to address students' moral and conventional transgressions, (2) whether those responses were appropriate for the type of transgression, and (3) the type of reflection promoted by the teachers on issues related to the socio-moral domains. Findings evidenced that the most prevalent responses did not allude to moral or conventional issues, and did not include a reflection with student participation. Practical implications of the study are discussed in terms of the need of more evidence-based guidelines and training for educators about how to promote moral development in their classrooms.